Effect of Heating Temperature on Strength of Rice Straw Bio-board - ZHANG, Jin; WANG, Xiulun; KITO, Koji (Journal of Environmental Conservation Engineering, 2016)
The main objective of this study was to investigate the possibility of making bio-board(biodegradable biomass board) using rice straw and the relationship between heating temperature and strength of bio-board. The making process included cutting, soaking, refining, forming and drying. Strength of the bio-board was measured by three-point bending test and tensile test. The result showed that making process of bio-board was appropriate. In addition, the maximum value of average rupture stress of bending test under the different experimental conditions was 18.50 MPa and the maximum value of average rupture stress of tensile test was 12.46 MPa, both of which appeared at temperature of 190℃. The result obtained that heating temperature affected the strength of bio-board. The rupture stress increased with the increase of heating temperature. Moreover, the strength of bio-board is suitable for the uses of agriculture, packaging materials and so on.